The thiocyanate degradation by fungi isolated from mining environments and evaluation of degradative capacity - Medina, Susan (2012)
used in gold production this compound is very toxic especially for environment, by nature reaction with sulfur it converts into thiocyanate (-SCN). In this paper, we isolate -SCN degrading fungus from Junin and Tumbes mining zones. Strains were assayed on 5 to 600 mM -SCN concentration, at least thiocyanate degrading kinetic was assayed at 1.2 g.L-1 of KSCN initial concentration, then the best strains had been morphological, biochemical and molecular identified using ITS RNA molecular marker. From 58 isolated fungus we found 4 unparfait funguses with a great thiocyanate degrading capacity those strains could be used for bioremediation processes. Thiocyanate degrading capacity of these strains was 50 g.L-1 on plate into 72 hours and their average capacity was 10.05 mg.L-1 -SCN with an standard velocity of -SCN degradation of 28.77 mg.L-1.h-1. Two strains were molecular identified as Fusarium trincictum by using ITS rDNA gene.